Le paysage comme possibilité : la leçon du paysagiste américain Garrett Eckbo - Marta Ortolani (Projets de Paysage)
Contemporary rural landscapes, namely those in Southern Europe, are impacted by significant migratory phenomena. The Mediterranean migratory model has become a structural component of transformation processes with spatial repercussions including the emergence of informal settlements, especially in the south of Italy. This article describes the spatial characteristics of these settlements, referred to as “ghettos”, and examines the case of La Pista Borgo Mezzanone in the region of Puglia. It considers the role that landscape architecture can play in such a context. The question is analysed by drawing on the theories and projects of the American landscape architect Garret Eckbo, who worked in the 1940s in a context that was similar in many ways. The case studies are part of a theoretical framework centred on the concept of the landscape and landscape architecture based on the reflections of John B. Jackson who distinguished two modalities in landscape architecture which were the political and the vernacular, and on contemporary research in landscape urbanism (Charles Waldheim, James Corner). These theoretical contributions underscore the research problem by focusing on the tools that make it possible to identify spatial configurations conducive to the establishment and development of a community in a changing territorial context. The objective is to identify possible solutions for the building of new spatial configurations through landscape urbanism.